Intra‐population variation in reproductive timing covaries with thermal plasticity of offspring performance in perch Percafluviatilis. Issue 10 (7th June 2021) - Hall, Marcus; Nordahl, Oscar; Larsson, Per; Forsman, Anders; Tibblin, Petter
Abstract: Life history theory posits that organisms should time their reproduction to coincide with environmental conditions that maximize their fitness. Population‐level comparisons have contributed important insights on the adaptive value of reproductive timing and its association to environmental variation. Yet, despite its central role to ecology and evolution, the causes and consequences of variation in reproductive timing among individuals within populations are poorly understood in vertebrates other than birds. Using a combination of observational field studies and a split‐brood experiment, we investigated whether differences in breeding time were associated with changes in hatching success, reproductive allocation and reaction norms linking offspring performance to temperature within an anadromous Baltic Sea population of perch Perca fluviatilis . Field observations revealed substantial variation in reproductive timing, with the breeding period lasting almost 2 months and occurring in temperatures ranging from 10 to 21℃. The hatching success of perch decreased as the reproductive season progressed. At the same time, the reproductive allocation strategy changed over the season, late breeders (the offspring of which were introduced into a high resource environment and increased predation pressure) produced more and smaller eggs that resulted in smaller larvae, compared with early breeders. The split‐brood experiment in which eggs were incubated in different temperatures (10, 12, 15, 18°C) showed that differences in reproductive timing were associated with a change in the shape of the reaction norm linking offspring performance to water temperature indicative of adaptive phenotypic plasticity, with the offspring of early breeders performing best in low temperatures and the offspring of late breeders performing best in high temperatures. The seasonal changes in reproductive traits and the shape of the thermal performance suggest time‐dependent adaptive differences among individuals within the population. Management actions aimed at preserving and restoring variation in the timing of reproductive events will thus likely also influence variation in associated life history traits and thermal performance curves, which could safeguard populations against environmental challenges and changes associated with exploitation and global warming. Abstract : Reproductive timing often varies among individuals within populations and, in seasonal environments, this result in that the offspring is exposed to different thermal conditions. Here, by studying perch, the authors uncover seasonal changes in reproductive traits and the thermal performance in offspring indicative of adaptive plasticity.